EFFECT OF HEALTH EDUCATION ON PREECLAMPSIA KNOWLEDGE AND ATTITUDE TOWARDS PREGNANT WOMEN PUTRI AYU CITY PUBLIC HEALTH IN JAMBI - Mila Triana Sari; Yati Atrawani (Jurnal Akademika Baiturrahim Jambi, 2018)
Preeclampsia is a major cause of morbidity and mortality of mothers and babies in the world. The frequency of occurrence of preeclampsia in Indonesia about 3-10%. In Indonesia preeclampsia, and eclampsia preeklampsi weight is the leading cause of maternal mortality ranges from 15% to 25%, while the infant mortality between 45% to 50%. The purpose of this study to determine the effect of health education on the knowledge and attitudes of preeclampsia pregnant women in Jambi Kota Putri Ayu PHC 2016. This research is a pra eksperimen one group pretest posttest. The population in this study is the first trimester pregnant women in Jambi Kota Putri Ayu PHC as much as 10 pregnant women. Sampling was done by total sampling technique as much as 10 respondents. The data collection was done on August 9 to 30 in 2016 using a questionnaire. The analysis is univariate and bivariate. The results showed that the knowledge of pregnant women before being given health education that nine pregnant women (90%) had low knowledge and health education are given after 6 pregnant women (60%) had low knowledge. The attitude of pregnant women before being given health education ie 7 pregnant women (70%) have a negative attitude and a pregnant woman who has a positive attitude that is three pregnant women (30%) and after given health education is one pregnant women (10%) have a negative attitude , The analysis results obtained There is an effect of health education on the knowledge of pre-eclampsia in pregnant women Jambi Kota Putri Ayu PHC 2016 and health education There is an effect of preeclampsia on the attitudes of pregnant women in Jambi Kota Putri Ayu PHC 2016.